Eser A. The future of work — flexibility and efficiency of virtual work / trans. from Engl. I. V. Tsygankova - I. V. Tsygankova (Омский научный вестник: Серия "Общество. История. Современность")
The article considers virtual employment as a new phenomenon in the labor market. The author formulates its characteristics and peculiarities, reveals advantages and disadvantages of virtual employment, obstacles to its development. The characteristic of the main software products allowing to organize effectively work in virtual space is given, their comparative analysis is carried out